Polypoid Carcinoma of the Oropharynx with Stromal Ossifying Myofibroblastic Proliferation: A Case Report and Literature Review - Marcello Filotico; Alessandro D'Amuri (Hindawi Limited, 2016)
A 76-year-old man reported a worsening difficulty in swallowing, leading to the inability to eat. Physical examination and CT scan revealed a polypoid mass on the posterior oropharynx and obstructing the oropharyngeal space. Histologically, the surface was ulcerated. In the underlying necrotic rim, there was active granulation tissue, and a proliferation of voluminous, globoid elements with hyperchromatic and irregular nucleus, sometimes arranged in a alveolar aggregate. The core of the lesion contained spindle-like myoid elements in interwoven bundles, with trabeculae of osteoid matrix maturing into calcified bone. Immunohistochemistry documented positivity for cytokeratins, epithelial membrane antigen, and P63 in the globoid elements beneath the necrotic rim; strong and diffuse expression of vimentin, smooth muscle actin, and CD99 and BCL2 in the spindle elements; and complete negativity for cytokeratin 5/6, high molecular weight cytokeratin (clone 34βE12), S100, muscle-specific actin, desmin, CD117, and anaplastic lymphoma kinase. The lesion was morphologically and immunophenotypically classified as a polypoid oropharyngeal carcinoma with ossifying myofibroblastic stromal proliferation.